Church Offices and Social Promotion of the Families of Urban Elite in the Communal Societies of Eastern Adriatic - Nikolić, Zrinka (2003)
In this paper I try to explore in what way relations with the church influenced the position of elite families in three Dalmatian towns - Zadar, Trogir and Split in the time period from the beginning of the twelfth until the middle of the fourteenth century. The general question is: could ecclesiastical career of certain individuals launch family into more prominent circles, help them socially and perhaps also economically, or are prominent ecclesiastics to be seen more as a consequence of their prominent family background? So far the research points more to the second possibility. Special attention is placed on bishops and archbishops as leading ecclesiastics but other church offices (archdeacons, other canons and parish priests, abbots and abbesses) would be considered as well. It is also interesting to see whether certain families show more inclination to service in Church than others, and whether this is true and we could consider a certain family politics through Church. Possible attachment of families to certain church institutions, for example, to particular monasteries either as cenobites, advocates or donors, is also explored. Patronage rights still show strong acknowledgment of cognatic family relations in the society of this period.